The evolution of money - Ederer, Rupert J. (Washington: Public Affairs Press, 1964)
The book considers the origin of money and the major stages in the development of money the barter stage, the use of commodities as money and the use of money. It also examine the changing scope of government monetary activities.
Includes index
Bibliography: p. 144-150.
usc 13/11/18
Loans
Keywords: Money